Association between pediatric obesity and foot morphology: insights from a large-scale cross-sectional study using photogrammetry - Hakan Büyükçelebi; Mahmut Açak; Özgür Eken; Adem Doğaner; Gökmen Özen; Luca Paolo Ardigò (BMC Pediatrics)
Abstract Background Childhood obesity is a critical public health concern with implications for musculoskeletal development. Foot posture abnormalities—particularly pes planus—may be associated with obesity and could serve as early diagnostic indicators. Aim This study investigated the relationship between foot posture and obesity in children aged 4–14 years using non-invasive assessment methods. Materials and methods A total of 7,908 children (mean age: 8.7 ± 2.9 years; 51.2% male) were assessed using photogrammetry and the Staheli Arch Index, along with the Jack Test to classify foot posture. BMI categories and foot posture types were statistically compared. Results Rigid pes planus was found in 9.6% of children, flexible pes planus in 7.8%, and high arch in 3.8%. Among overweight and obese children, the prevalence of rigid pes planus was significantly higher (p < 0.001). Logistic regression revealed that rigid pes planus increased the risk of obesity by 7.2 times (OR = 7.156; 95% CI: 5.179–9.887). Conclusion Rigid pes planus is strongly associated with obesity in children. Foot posture screening, especially in early childhood, may serve as a valuable tool for identifying children at risk for obesity-related complications and guiding early preventive interventions.